Vitamin D3 supplementation in patients with chronic obstructive pulmonary disease (ViDiCO): a multicentre, double-blind, randomised controlled trial. Issue 2 (February 2015) - Martineau, Adrian R; James, Wai Yee; Hooper, Richard L; Barnes, Neil C; Jolliffe, David A; Greiller, Claire L; Islam, Kamrul; McLaughlin, David; Bhowmik, Angshu; Timms, Peter M; Rajakulasingam, Raj K; Rowe, Marion; et al.
Summary Background Patients with chronic obstructive pulmonary disease (COPD) often have vitamin D deficiency, which is associated with increased susceptibility to upper respiratory infection—a major precipitant of exacerbation. Multicentre trials of vitamin D supplementation for prevention of exacerbation and upper respiratory infection in patients with COPD are lacking. We therefore investigated whether vitamin D3 (colecalciferol) supplementation would reduce the incidence of moderate or severe COPD exacerbations and upper respiratory infections. Methods We did a randomised, double-blind, placebo-controlled trial of vitamin D3 supplementation in adults with COPD in 60 general practices and four Acute National Health Service Trust clinics in London, UK. Patients were allocated to receive six 2-monthly oral doses of 3 mg vitamin D3 or placebo over 1 year in a 1:1 ratio using computer-generated permuted block randomisation. Participants and study staff were masked to treatment assignment. Coprimary outcomes were time to first moderate or severe exacerbation and first upper respiratory infection. Analysis was by intention to treat. A prespecified subgroup analysis was done to assess whether effects of the intervention on the coprimary outcomes were modified by baseline vitamin D status. This trial is registered with ClinicalTrials.gov, number NCT00977873. Findings 240 patients were randomly allocated to the vitamin D3 group (n=122) and placebo group (n=118). Vitamin D3 compared with placebo did not affect time to first moderate or severe exacerbation (adjusted hazard ratio 0·86, 95% CI 0·60–1·24, p=0·42) or time to first upper respiratory infection (0·95, 0·69–1·31, p=0·75). Prespecified subgroup analysis showed that vitamin D3 was protective against moderate or severe exacerbation in participants with baseline serum 25-hydroxyvitamin D concentrations of less than 50 nmol/L (0·57, 0·35–0·92, p=0·021), but not in those with baseline 25-hydroxyvitamin D levels of at least 50 nmol/L (1·45, 0·81–2·62, p=0·21; p=0·021 for interaction between allocation and baseline serum 25-hydroxyvitamin D status). Baseline vitamin D status did not modify the effect of the intervention on risk of upper respiratory infection (pinteraction=0·41). Interpretation Vitamin D3 supplementation protected against moderate or severe exacerbation, but not upper respiratory infection, in patients with COPD with baseline 25-hydroxyvitamin D levels of less than 50 nmol/L. Our findings suggest that correction of vitamin D deficiency in patients with COPD reduces the risk of moderate or severe exacerbation. Funding UK National Institute for Health Research.